2013
DOI: 10.4103/1319-2442.121276
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of microalbuminuria among children and adolescents with insulin-dependent diabetes mellitus

Abstract: Microalbuminuria precedes the onset of diabetic nephropathy in insulin-dependent diabetes mellitus (IDDM) pediatric patients. Its prevention is among the most important challenges in managing IDDM. We attempted to determine the occurrence of microalbuminuria among IDDM Saudi children and adolescents and its associated risk factors. This is a retrospective cross-sectional study conducted on 409 IDDM children and adolescents attending the pediatric clinic at King Abdul-Aziz University Hospital from 2006 to 2010.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
2
12
0
1
Order By: Relevance
“…A significant difference was found regarding the duration of T2DM which is in agreement with other studies that found a significant difference between normo-and microalbuminuric groups regarding duration of diabetes mellitus. [15][16][17] The results for FBG, RBG, HbA1C, serum creatinine, eGFR, urinary albumin/creatinine ratio, serum albumin and total plasma proteins were in agreement with another study, which documented a significant difference between both diabetic groups regarding the previous parameters. 18 Another study reported that progression of diabetic nephropathy was accompanied by declining GFR and increasing urinary albumin excretion.…”
Section: Discussionsupporting
confidence: 89%
“…A significant difference was found regarding the duration of T2DM which is in agreement with other studies that found a significant difference between normo-and microalbuminuric groups regarding duration of diabetes mellitus. [15][16][17] The results for FBG, RBG, HbA1C, serum creatinine, eGFR, urinary albumin/creatinine ratio, serum albumin and total plasma proteins were in agreement with another study, which documented a significant difference between both diabetic groups regarding the previous parameters. 18 Another study reported that progression of diabetic nephropathy was accompanied by declining GFR and increasing urinary albumin excretion.…”
Section: Discussionsupporting
confidence: 89%
“…The second T1DM group consisted of children with newly diagnosed diabetes (T1DM-ND). Only two diabetic patients of the T1DM-T group had microalbuminuria which serves as an early marker of diabetic nephropathy (Al-Agha et al 2013). The concentration of the circulating and urinary biochemical parameters of the Arg/NO pathway measured in our children with T1DM and healthy non-diabetic controls and the results of the statistical analyses are summarized in Table 2 (T1DM-T vs HC), Table 3 (T1DM-ND vs HC) and Table 4 (T1DM-T vs T1DM-ND).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early detection and intervention for renal lesions of DN is necessary before the lesions advance to irreversible levels. Microalbuminuria (MAU) level, the current diagnostic gold standard for DN [1], also represents an index of diabetic renal damage severity [2][3][4]. Persistently high MAU may suggest the advent of stage III of DN, which is the result of progressive glomerulosclerosis due to long-term hyperfiltration.…”
Section: Introductionmentioning
confidence: 99%